2017
DOI: 10.1371/journal.pone.0185273
|View full text |Cite
|
Sign up to set email alerts
|

Broad recruitment of mGBP family members to Chlamydia trachomatis inclusions

Abstract: Chlamydia, the most common sexually transmitted pathogen, is an exquisitely adapted Gram-negative obligate intracellular bacterium. Intracellular Chlamydia trachomatis replicate in a specialized vacuole, termed inclusion, which shields the bacterium from antimicrobial immunity of the host cells and acts as a signalling interface. Previously it was shown that members of the interferon induced guanylate binding protein (mGBP) family, in particular murine GBP1 and mGBP2, were found to accumulate at the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…These findings ascribe additional biological relevance to GBP1 lipidation as demonstrated from in vitro experiments with unilamellar vesicles and association with phagosomes (Shydlovskyi et al , ) and STm in HeLa cells (Bradfield, ). A similar role for lipidation of GBP5 for its recruitment to LPS OMVs and mouse Gbp1/2 for trafficking to microbial vacuoles has been identified previously (Finethy et al , ; Lindenberg et al , ; Santos et al , ). The correlation of microbe‐targeting and cell death in our studies mirrored similar findings on mouse and human GBPs that target bacteria and restrict their replication in a GTPase‐ and isoprenylation‐dependent manner (Kim et al , ; Finethy et al , ; Li et al , ; Piro et al , ; Wandel et al , ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings ascribe additional biological relevance to GBP1 lipidation as demonstrated from in vitro experiments with unilamellar vesicles and association with phagosomes (Shydlovskyi et al , ) and STm in HeLa cells (Bradfield, ). A similar role for lipidation of GBP5 for its recruitment to LPS OMVs and mouse Gbp1/2 for trafficking to microbial vacuoles has been identified previously (Finethy et al , ; Lindenberg et al , ; Santos et al , ). The correlation of microbe‐targeting and cell death in our studies mirrored similar findings on mouse and human GBPs that target bacteria and restrict their replication in a GTPase‐ and isoprenylation‐dependent manner (Kim et al , ; Finethy et al , ; Li et al , ; Piro et al , ; Wandel et al , ).…”
Section: Discussionsupporting
confidence: 75%
“…The human genome harbors 7 GBP genes, among which GBP1‐5 are the most ubiquitously expressed members and GBP6 and 7 are only found in epithelial cells lining mucosal surfaces of the lung and intestines (Uhlen et al , ). In contrast, the mouse genome encodes 11 Gbps at two separate chromosomal loci (chr 3 and chr 5), whose protective roles have been revealed through studies on mice lacking Gbp1, Gbp2, Gbp5, or all Gbps on Chr3 (Degrandi et al , , ; Kim et al , ; Shenoy et al , ; Yamamoto et al , ; Lindenberg et al , ). Mouse mGbp1, 2, 3, 5, 6, 7, 9, and 10 can be recruited to vacuoles of bacteria such as Salmonella, Listeria, Francisella, Mycobacterium, Chlamydia, and Legionella (Kim et al , ; Degrandi et al , ; Haldar et al , ; Meunier et al , , ; Feeley et al , ; Finethy et al , ; Lindenberg et al , ) or parasites such as Toxoplasma gondii ( Tg ; Degrandi et al , ; Virreira Winter et al , ; Kravets et al , , ; Selleck et al , ; Haldar et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…During some intracellular infections, GBPs are recruited to pathogen-containing vacuoles, as observed during Toxoplasma, Mycobacterium bovis, and C. trachomatis infection, or directly to bacterial membranes in the case of cytosolic Francisella or Shigella infection [3,20,21,34,35]. Models suggest GBPs can restrict pathogens by exposing bacterial ligands from pathogen-containing vacuoles or directly from cytosolic bacteria for sensing by the inflammasome [19][20][21]36].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Just recently, further GBPs were shown to be recruited to the Ctr inclusion in murine cells stimulated with IFNγ, but their effect on chlamydial growth restriction was not demonstrated (Lindenberg et al, 2017). However, the mechanism by which IRGs and GBPs detect and destroy the chlamydial inclusion is still under investigation.…”
Section: Recognition Of the Inclusion By Cell-autonomous Defence Mementioning
confidence: 99%
“…Moreover, Haldar and colleagues revealed that immune attack of the inclusion by the above‐mentioned effectors is highly dependent on components of the autophagy machinery (Haldar, Piro, Pilla, Yamamoto, & Coers, ). Just recently, further GBPs were shown to be recruited to the Ctr inclusion in murine cells stimulated with IFNγ, but their effect on chlamydial growth restriction was not demonstrated (Lindenberg et al, ). However, the mechanism by which IRGs and GBPs detect and destroy the chlamydial inclusion is still under investigation.…”
Section: Recognition Of the Inclusion By Cell‐autonomous Defence Mechmentioning
confidence: 99%